The Nine-banded Armadillo (Dasypus novemcinctus) - Joseph M. Schaefer; Mark E. Hostetler (EDIS, 2003)
Armadillos are prehistoric-looking animals that belong to a family of mammals found primarily in Central and South America. The earliest fossil ancestor of our North American armadillo occurred about 60 million years ago; it was as large as a rhinoceros. Our present-day nine-banded or long-nosed armadillo, Dasypus novemcinctus, is much smaller; adults normally weigh from 8-17 pounds (3.5-8 kilograms). This species occurs in Texas and east, throughout the South. It occasionally is found in Missouri and South Carolina. However, cold weather limits the northern boundary of the armadillo's range. This document is WEC 76 and was previously published under the title "Control of Armadillos." It is one of a series of the Department of Wildlife Ecology and Conservation, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences (IFAS), University of Florida. First published: January 1998. Reviewed: 2001. Major revision: October 2003.